Soil bacteria are more sensitive than fungi in response to nitrogen and phosphorus enrichment - Chen, Youchao; Yin, Shuwei; Shao, Yun; Zhang, Kerong (Frontiers in Microbiology, 2022)
Anthropogenic activities have dramatically increased nitrogen (N) and phosphorous (P) enrichments in terrestrial ecosystems. However, it is still unclear on how bacterial and fungal communities would respond to the simultaneously increased N and P enrichment. In this study, we used a field experiment to simulate N and P input, and examined the effects of N and P additions on the abundance, alpha-diversity, and community composition of soil bacteria and fungi in a riparian forest. Six nutrient-addition treatments, including low N (30 kg N ha-1 year-1), high N (150 kg N ha -1 year-1), low P (30 kg P2O5 ha-1 year-1), high P (150 kg P2O5 ha -1 year-1), low N+P, high N+P, and a control (CK) treatment were set up. We found that the N and P additions significantly affected bacterial abundance, community composition, but not the alpha diversity. Specifically, 16S, nirK, and nirS gene copy numbers were significantly reduced after N and P additions, which were correlated with decreases in soil pH and NO- 3-N, respectively; Co-additions of N and P showed significantly antagonistic interactions on bacterial gene copies; Nutrient additions significantly increased the relative abundance of Proteobacteria while reduced the relative abundance of Chloroflexi. Mantel’s test showed that the alteration in bacterial composition was associated with the changes in soil pH and NO- 3-N. The nutrient additions did not show significant effects on fungal gene copy numbers, alpha diversity, and community composition, which could be due to nonsignificant alterations in soil C/N and total P concentration. In conclusion, our results suggest that soil bacteria are more sensitive than fungi in response to N and P enrichment; the alterations in soil pH and NO- 3-N explain the effects of N and P enrichment on bacterial communities, respectively; and the co-addition of N and P reduces the negative effects of these two nutrients addition in alone. These findings improve our understanding of microbial response to N and P addition, especially in the context of simultaneous enrichment of anthropogenic nutrient inputs.